Spontaneous regression of mantle cell lymphoma: a report of four cases. Issue 1 (29th May 2018) - Ye, Haige; Desai, Aakash; Gong, Tiejun; Zeng, Dongfeng; Nomie, Krystle; Chen, Wendy; Wang, Wei; Romaguera, Jorge; Wang, Michael L.
Abstract: Background: Spontaneous regression has been reported in some indolent forms of lymphoma. Mantle cell lymphoma (MCL) is an aggressive lymphoid neoplasm and has a poor prognosis. However, approximately 30% of MCL patients can exhibit indolent clinical behavior. To date, complete spontaneous regression of MCL has not been reported. Case presentation: We describe four cases of spontaneous regression of MCL. At the time of presentation, these patients were asymptomatic, with lymph node enlargement and mild to moderate fluorodeoxyglucose (FDG) uptake on FDG‐positron emission tomography combined with computed tomography. One of the possible mechanisms of spontaneous regression of the tumor could be due to the host immune response through humoral and cellular immunity, which may have a role in the clearance of tumor cells. Conclusions: In this report, we support the use of a "wait and watch" strategy for MCL patients with no risk factors and indolent behavior. This strategy helps spare patients from further potentially harmful chemotherapy. In addition, we describe the phenomenon of spontaneous regression in MCL patients who are asymptomatic and have low‐volume disease.